Analisis Debit Banjir Sungai Daik Dengan Berbagai Kala Ulang - Rahman Wahidin Miatullah; Manyuk Fauzi; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Daik River in Lingga Regency is one of the flood prone rivers. To overcome this, information about the capacity that can be accommodated by the Daik River is needed. Therefore, the researcher simulated the water surface profile intended to provide information about the flood discharge into the Daik river. Theflood discharge plans were calculated with a return period of 2 years, 5 years, 10 years, 20 years, 25 years, 50 years, 100 years by using Hesper method. The simulation results show that in most parts of the DaikRiver at the time of the return of 2 years there has been a flood inundation with an flood discharge of 159,3909 m3/s, while the cross-section of Daik River capacity of 57,53 m3/s.Keywords: daik river, flood discharge plans, HEC-RAS.